High-dose ferric citrate supplementation attenuates omega-3 polyunsaturated fatty acid biosynthesis via downregulating delta 5 and 6 desaturases in rats with high-fat diet-induced obesity. Issue 23 (17th November 2021) - Faradina, Amelia; Tseng, Sung-Hui; Tung, Te-Hsuan; Huang, Shih-Yi; Lee, Yu-Chieh; Skalny, Anatoly V.; Tinkov, Alexey A.; Chen, Seu-Hwa; Chuang, Yung-Kun; Chang, Jung-Su
Abstract : High dose ferric citrate supplementation attenuated n-3 PUFAs biosynthesis in rats with HFD-induced obesity via downregulating Δ-6 and Δ-5 desaturases. Decreased n-3 PUFAs and the converting enzymes were correlated with levels of liver iron and MDA. Abstract : Obesity is associated with an increased risk of an iron deficiency; however, a synergistic relationship between iron and lipid homeostasis was also observed. The aim of this study was to investigate the effects of pharmacological doses of iron supplementation on omega 3 (n-3) and omega 6 (n-6) polyunsaturated fatty acids (PUFAs). Sprague-Dawley (SD) rats were fed a normal diet or a 50% high-fat diet (HFD) without or with pharmacological doses of ferric citrate (0.25, 1, or 2 g ferric iron per kg diet) for 12 weeks, and erythrocyte profiles of n-3 and n-6 PUFAs were quantitated. Ferric citrate supplementation showed dose-related effects on liver inflammation, liver iron accumulation, and increasing circulating levels of iron, erythrocyte degradation biomarkers LVV-hemorphin-7, malondialdehyde (MDA), and insulin. Obese rats supplemented with 2 g ferric iron per kg diet also had decreased levels of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and total n-3 PUFAs compared to rats fed a normal diet or HFD alone. A western blotting analysis revealed that iron-mediated downregulation of n-3 PUFA-converting enzymes (Δ5 and Δ6 desaturases) only occurred at high dosages (≥1 g ferric iron per kg diet). A Spearman correlation analysis showed that total liver iron and serum LVV-hemorphin-7 and MDA were negatively correlated with n-3 PUFAs and their converting enzymes (Δ5 and Δ6 desaturases) (all p < 0.05). In conclusion, obese rats that received high-dose ferric citrate supplementation (>1 g of ferric iron per kg diet) exhibited decreased n-3 PUFA levels via downregulation of expressions of Δ5 and Δ6 desaturase enzymes.